Strategy Formulation and Implementation for PT.Multigarmen Jaya - Yoanita, Martha; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
- The objective of this Â final project is to formulate and proposed the strategy forÂ PT.Multigarmen Jaya (PT.MGJ) to faced the tight competition in garment industries. The analysis begins from environmental analysis that consist of external and internal analysis. For external analysis used PEST, Porter five forces, and competitor analysis, and for internal analysis used value chain analysis and resources analysis. From that analysis, there are several problems discovered, such as competitor threats from within and outside the country, delays in raw material delivery, and errors often occur in delivery. There are three kinds of strategy proposed to PT.MGJ. Based on corporate strategy analysis, PT.MGJ is classified into growth strategy alternative, and for that matter, vertical integration strategy was selected to create an enhancement in delay on raw material. Business strategy on PT.MGJ is integration cost leadership/ differentiation, where the goal from this strategy is to efficiently produce products with some differentiated features. And the last is functional strategy which is result from TOWS matrix. Besides, there are implementation plan for each strategies. The implementation strategy is divided into some activities in proposed value chain, which consists of inbound logistics, operations, outbound logistics, marketing and sales, as well as supporting activities. There was also a proposal to establish cooperation with suppliers of raw materials fabric with strategic alliance.Â Keywords: garment industry, PEST, Porter five forces, value chain analysis, integration cost leadership/ differentiation, strategic alliance, TOWS matrix